Журнал «пізнайко»: становлення видання та жанрова палітра матеріалів - Галаджун, Зоряна; Юзефович, Дарина; Haladzhun, Zoriana (Видавництво Львівської політехніки, 2018)
Простежено історію зародження та розвитку журналу для дітей «Пізнайко», виокремлено основні етапи його становлення. Крім того, на текстах видання проаналізовано та виокремлено жанри, що використовують автори журналу для доступного та відповідного до віку представлення матеріалу дитячій аудиторії.

A number of children’s periodicals has increased significantly in recent times. There are more than 70 kinds of children’s magazines and newspapers within the Ukrainian press. They currently can satisfy even the most demanding readers because of their diversity. Modern children do not remain indifferent to social events and hope to find answers to their questions in their favourite magazines and newspapers in particular. They partially substitute books for children, their parents at leisure, teach and educate, that is they help to form child’s world outlook through the information he or she acquires. Thus, investigation and study of topical issues associated with magazines and newspapers meant for children is of utmost importance. Considering that press for children is a part of their leisure, it is important to study its genre palette. General scientific methods of analysis, synthesis, generalization have been applied. Descriptive and comparative historical methods have been applied at different stages of work. As a result of the undertaken study we have managed to single out the following stages of the «Piznayko» magazine establishment: inception of the idea is considered to be the first stage with the timeframe of the nineties; the second stage begins in February of 1997 when the Russian-language edition of the «Poznayko» magazine was founded, timeframe – 1997-2001; the third stage began when the English-language edition of «Posnayko» was created, timeframe – January 2001-January 2005; the fourth stage began when the first issue of the «Piznayko from 2 to 5» (currently «Piznayko from 2 to 6») came out in January of 2005, timeframe – January 2005-January 2013; the fifth stage began in January of 2013 with the close of the English-language edition, continued with the close of the Russian-language edition in January of 2015, and still lasts. Analysis of genre diversity of the «Piznayko» magazine has shown all the peculiarities of the edition and made it clear that the magazine under study is scarcely different from the other publications for children, at least as far as genre correlation and completeness are concerned. There is a lot of game genres here: from anecdotes to crossword puzzles. Besides, authors make use of news genres that are slightly modified, though basic requirements and features are preserved. Paragraphs, articles and interviews are the most prominent news genres on the pages of the magazine. Most of the edition’s material is presented in the following literary and art genre forms: poems, narratives, novels and excerpts from fairy-tales. Originality lies in the fact that the first periodization attempt of establishment and genre palette of the «Piznayko» magazine has been made. Despite considerable competition, the «Piznayko» magazine continues to come out, undergoes modifications and transformations, and looks for new approaches and methods to catch the interest of more and more readers.
«piznayko» (magazine): establishment of the publication and genre palette of materials
Keywords: дитяча преса України; становлення дитячого видання; журнал «Пізнайко»; жанрові форми у дитячому виданні; Ukrainian press for children; establishment of the edition for children; the «Piznayko» magazine; genre forms in children’s edition; 070-053.2(477) «19/20»(091)